Model of Determinant Factors Affecting Older People Quality of Life Among Suburban Elderly in Riau, Indonesia - Handayani Handayani; Ligat Pribadi Sembiring; Haidatul Indriani; Muhammad Rendi Alfarez; Shafira Garnetta (Future Science, 2024)
Elderly people are one of the susceptible communities that should not be neglected because of their vulnerability to suffering diseases due to the aging process. It needs contributions from family cooperation, cadres and health workers’ care, and local government support. This study aimed to elaborate on determinant factors affecting older people’s quality of life among suburban elderly in Riau Province, Indonesia. There were 42 elderly being interviewed using OPQoL and other questionnaires. Data was examined using SPSS and Smart PLS. Independent variables were age, gender, level of education, marital status, and type of housemate. level of income, smoking habit, exercise activity, body mass index, abdominal circumference, knowledge score, level of health perception, health security, and each score consisting of activity of daily living (Barthel index), depression status (Geriatric Depression Scale), cognitive status (Abbreviated Mental Test and Mini Mental State Examination), fall risk (Hendrich and Morse Fall Scale), mini nutritional assessment, family support, quality of life using OPQoL and SF-36 questionnaires. Only four variables acting as determinant factors to older people's quality of life i.e health security (p 0.004), health perception (0.006), AMT score (0.031) and social function score (p 0.016) proved by a formula using linear regression (p 0.007). It is concluded that health security, health perception and AMT score will in-crease OPQoL score, however, the social function score will decrease it.